Are critically endangered fish back on the menu? Analysis of U.K. fisheries data suggest post-ban landings of prohibited skates in European waters. (July 2016) - Simpson, Samantha J.; Sims, David W.
Abstract: Skates (Rajidae) have been commercially exploited in Europe for hundreds of years with some species' abundances declining dramatically during the twentieth century. In 2009 it became "prohibited for EU vessels to target, retain, tranship or land" certain species in some ICES areas, including the critically endangered common skate and the endangered white skate. To examine compliance with skate bans the official UK landings data for 2011–2014 were analysed. Surprisingly, it was found that after the ban prohibited species were still reported landed in UK ports, including 9.6 t of common skate during 2011–2014. The majority of reported landings of common and white skate were from northern UK waters and landed into northern UK ports. Although past landings could not be validated as being actual prohibited species, the landings' patterns found reflect known abundance distributions that suggest actual landings were made, rather than sporadic occurrence across ports that would be evident if landings were solely due to systematic misidentification or data entry errors. Nevertheless, misreporting and data entry errors could not be discounted as factors contributing to the recorded landings of prohibited species. These findings raise questions about the efficacy of current systems to police skate landings to ensure prohibited species remain protected. By identifying UK ports with the highest apparent landings of prohibited species and those still landing species grouped as'skates and rays', these results may aid authorities in allocating limited resources more effectively to reduce landings, misreporting and data errors of prohibited species, and increase species-specific landing compliance. Highlights: In 2009 some species of endangered skate were prohibited from being landed. Landings data post ban contains records of prohibited species sold in UK markets. Some areas have higher landings than others, notably the northern areas of the UK. Records may be actual landings, misidentification of species or error in data input. Results can help allocate surveillance resources more effectively for species conservation.